A systematic review of approaches to quantify hydrologic ecosystem services to inform decision-making. Issue 3 (2nd July 2016) - Harrison-Atlas, Dylan; Theobald, David M.; Goldstein, Joshua H.
ABSTRACT: Global threats to freshwater resources are prompting widespread concern about their management and implications for well-being. In recent decades, hydrologic ecosystem services (HES) have emerged as an innovative concept to evaluate freshwater resources, providing opportunity for researchers to engage in decision-relevant science. We conducted a systematic review of studies published within the last decade, documenting approaches for mapping and quantifying HES and classifying the decision context. To gauge the relevance of HES science, we evaluated 49 case studies using multiple criteria for credibility, legitimacy, and saliency. We found compelling evidence that much of the variability in the quantification of HES can be explained by research motivations and scoping, reflecting the decision-oriented framing of the ecosystem services concept. Our review highlights key knowledge gaps in the state of the science including the need to articulate beneficiaries and to make connections to policy and management more explicit. To strengthen the potential for impact of HES science, we provide recommendations to assist researchers, practitioners, and decision-makers in identifying goals, formulating relevant questions, and selecting informative approaches for quantifying HES. We argue that sustained progress in applying HES requires critical evaluation and careful framing to link science and practice.